2019
DOI: 10.1515/humor-2019-0037
|View full text |Cite
|
Sign up to set email alerts
|

Coloring social change: Humor, politics, and social movements

Abstract: As many social movements demonstrate, humor can serve as an important resource to resist oppression, fight social injustice and bring social change. Existing research has focused on humor’s role within social movements and its positive effects on the free expression of criticism, reduction of fear, communication, mobilization of participants and so on. However, the current literature on the activist use of humor also expresses some reservations about its political efficacy. While humor may steam off the energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…While the question about the political efficacy of the protests, which may have been facilitated by the #presidentspartingwords discourse, lies outside the focus of this study, a word of caution is warranted here to avoid the oversimplification of the political implications of social media activism. A robust, and growing, research has recognized the potential of humor, irony, and parody—that is, the defining characteristics of ludic activism—to challenge power relations and to expand the repertoire of subversive political action (for review, see Takovski, 2020). Some scholars argue that humor may prove to be particularly effective in authoritarian contexts because, while constituting a relatively low-stakes action on the part of the oppressed, it simultaneously “hijacks the regime's narrative” (Camps-Febrer, 2012, p. 32) and deprives it of the possibility to legitimize its use of force in response to humorous provocations.…”
Section: Discussionmentioning
confidence: 99%
“…While the question about the political efficacy of the protests, which may have been facilitated by the #presidentspartingwords discourse, lies outside the focus of this study, a word of caution is warranted here to avoid the oversimplification of the political implications of social media activism. A robust, and growing, research has recognized the potential of humor, irony, and parody—that is, the defining characteristics of ludic activism—to challenge power relations and to expand the repertoire of subversive political action (for review, see Takovski, 2020). Some scholars argue that humor may prove to be particularly effective in authoritarian contexts because, while constituting a relatively low-stakes action on the part of the oppressed, it simultaneously “hijacks the regime's narrative” (Camps-Febrer, 2012, p. 32) and deprives it of the possibility to legitimize its use of force in response to humorous provocations.…”
Section: Discussionmentioning
confidence: 99%
“…Such humour research has been conducted on various types of discourse. Some researchers have investigated humour in formal discourse (Takovski, 2019;Tsakona, 2009;Urbatsch, 2022) as well as daily conversations (Gibbs et al, 2014;Hay, 2001;Priego-Valverde, 2021). In addition, multimodal discourse has also been employed as linguistic data for humour research (Breazu & Machin, 2022;Calhoun, 2019).…”
Section: Humour As a Research Topic In Linguistic Studiesmentioning
confidence: 99%
“…Calhoun (2019) carried out a multimodal discourse analysis to find out semiotic features of an anti-hegemonic racial comedy in the works of the most-followed person on Vine, a short-form video-sharing platform. Takovski (2019) combined content analysis and interviews to discuss the role of humour in a social movement and concluded that humour prompted free expression and engagement in the movement.…”
Section: Humour As a Research Topic In Linguistic Studiesmentioning
confidence: 99%
“…In particular, social media platforms proved crucial to public and activist efforts to (re)create a public in which criticism of the Gruevski government could circulate. As Biljana Bejkova (2020:222) explains, “new media and social networks provided ‘free zones’ where authorities did not have and could not install control and censorship.” These “free zone” social media publics enabled the popular opposition to organize and to circulate information (see Takovski 2019, cf. Bonilla and Rosa 2015).…”
Section: Discursive Engineering and The Enclosure Of The Macedonian P...mentioning
confidence: 99%